One summer in Sydney - Claydon, Annie (Harlequin medical romance, 2023)
A safe haven...a second chance? Escaping to Australia for a yearlong doctors' exchange is perfect for pediatrician Allie, who's working through the trauma of a past relationship. Finding support from her former and once-shy colleague Zac is the healing she needs. But while Zac has become a confident and surprisingly irresistible man, he carries his own scars. Despite knowing their handover is imminent, it seems to Allie that Zac isn't quite ready to leave...